Vasorin plays a critical role in vascular smooth muscle cells and arterial functions. Issue 10 (26th July 2022) - Louvet, Loïc; Lenglet, Gaëlle; Krautzberger, A. Michaela; Mentaverri, Romuald; Hague, Frédéric; Kowalewski, Clara; Mahtal, Nassim; Lesieur, Julie; Bonnet, Anne‐Laure; Andrique, Caroline; Gaucher, Céline; Gomila, Cathy; et al.
Abstract: Within the cardiovascular system, the protein vasorin (Vasn) is predominantly expressed by vascular smooth muscle cells (VSMCs) in the coronary arteries and the aorta. Vasn knockout ( Vasn −/− ) mice die within 3 weeks of birth. In the present study, we investigated the role of vascular Vasn expression on vascular function. We used inducible Vasn knockout mice ( Vasn CRE‐ERT KO and Vasn SMMHC‐CRE‐ERT2 KO, in which respectively all cells or SMCs only are targeted) to analyze the consequences of total or selective Vasn loss on vascular function. Furthermore, in vivo effects were investigated in vitro using human VSMCs. The death of Vasn CRE‐ERT KO mice 21 days after tamoxifen injection was concomitant with decreases in blood pressure, angiotensin II levels, and vessel contractibility to phenylephrine. The Vasn SMMHC‐CRE‐ERT2 KO mice displayed concomitant changes in vessel contractibility in response to phenylephrine and angiotensin II levels. In vitro, VASN deficiency was associated with a shift toward the SMC contractile phenotype, an increase in basal intracellular Ca 2+ levels, and a decrease in the SMCs' ability to generate a calcium signal in response to carbachol or phenylephrine. Additionally, impaired endothelium‐dependent relaxation (due to changes in nitric oxide signaling) was observed in all Vasn knockout mice models. Our present findings highlight the role played by Vasn SMC expression in the maintenance of vascular functions. The mechanistic experiments suggested that these effects are mediated by SMC phenotype switching and changes in intracellular calcium homeostasis, angiotensin II levels, and NO signaling. Abstract : Our present findings explain the dramatic effect of vasorin deletion on vascular function. The results of our mechanistic experiments suggest that these effects are mediated by smooth muscle cells phenotype switching and changes in calcium homeostasis, angiotensin II levels, and nitric oxide signaling